110k views
4 votes
Solve the system of equations. ​

Solve the system of equations. ​-example-1
User Chinito
by
5.5k points

1 Answer

3 votes

Answer:

x = -1

y = -2

Explanation:

The two equations are:


$ -4x + 3y = -2 \hspace{25mm} ........(1) $


$ y = x - 1 \hspace{25mm} .......(2) $

Substituting (2) in (1) we get:


$ -4x + 3(x - 1) = -2 $


$ \implies -4x + 3x - 3 = -2 $


$ \implies -x = 1 $

x = -1

Substituting the value of x in (2), we get

y = -1-1 = -2.

y = -2

User Ekse
by
6.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.